Discourses of power and counter-power in the Zimbabwean politico-religious communication in online news media - Mapuweyi, Nyasha; Wozniak, Janina (Intellect Ltd., 2021)
Christianity as the predominant religion in Zimbabwe consists of several faith groupings, each of which responds to public events through the mass media. Mainline churches uphold a conventional human rights approach to faith-based political criticism, while Mapostori or Apostolic churches follow an Africanist form of faith and appear to condone some alignment with the authoritarian ruling party. In the sampled media coverage of three online newspapers, the political use of religious strategies or practices from various faith groups by the president and high-ranking party functionaries is reported from either the former government-sanctioned view or an oppositional stance. Moralist reprimand is levied at various politicians from a religious rationale, assuming good and evil, church and state, Christianity and African spirituality, which, however, remain abstract since there is no overall faith-based guidance for political behaviour beyond a secular constitution that still appears utopian. The critical discourse analysis suggests that complex relationships exist among the various faiths, causing diverse religious interpretations of political events. This suspension of Cartesian thinking results in a continuing circular logic of blame and prayer, disaster and prophesy instead of the use of constitutional democratic institutions to hold politicians accountable. Such logic seems sustained by politicized interpretations of spiritual entities, spiritual interpretations of political events and by the perceptions of the Zimbabwean public, who, as believers of one or other faith, is equally at the mercy of opportunistic ‘prophets’ from many denominations as it is targeted by the political powers of the day.